Claudio Rodríguez Fer Brings the Antifascist Teacher and Poet Santiago Marcos Out of Obscurity - Paz Fentanes, Laura (Madrygal. Revista de Estudios Gallegos, 2023)
Review of Claudio Rodríguez Fer’s Santiago Marcos, poeta topo contra el fascismo (Barcelona, El Viejo Topo, 2023) by Laura Paz Fentanes.